2005
DOI: 10.1007/s11240-005-0513-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling available 2,4-dichlorophenoxyacetic acid in a tissue culture medium containing activated carbon

Abstract: Clonal propagation of high-value forest trees by somatic embryogenesis can help meet industry needs for uniform and high quality raw materials. Low embryogenic tissue initiation frequencies for loblolly pine (Pinus taeda L.) pose a limitation in work towards commercialization of this technology. At the time our research began most work on somatic embryo culture initiation in loblolly pine reported success in the range of 1-5%. Activated carbon (AC) has been reported to improve many tissue culture systems inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…A further increase of the concentration of activated charcoal did not increase the rate of TE differentiation, because the estimated means of TE differentiation on TIM 10 and TIM 20 were very similar to that of TIM 5 with 39.93 and 39.43%, respectively. It has been shown earlier that activated charcoal absorbs hormones such as 2,4-D or phenolic substances from the medium and plant cells (Pan and van Staden, 1998;von Aderkas et al, 2002;Toering and Pullman, 2005). We have found that TE differentiation in callus grown in light is inhibited on TIM 0 medium containing 4.5 lM 2,4-D (data not shown).…”
Section: Resultssupporting
confidence: 50%
“…A further increase of the concentration of activated charcoal did not increase the rate of TE differentiation, because the estimated means of TE differentiation on TIM 10 and TIM 20 were very similar to that of TIM 5 with 39.93 and 39.43%, respectively. It has been shown earlier that activated charcoal absorbs hormones such as 2,4-D or phenolic substances from the medium and plant cells (Pan and van Staden, 1998;von Aderkas et al, 2002;Toering and Pullman, 2005). We have found that TE differentiation in callus grown in light is inhibited on TIM 0 medium containing 4.5 lM 2,4-D (data not shown).…”
Section: Resultssupporting
confidence: 50%
“…On the other hand, (charcoal + 50 mg/l citric acid) treatment produced the minimum values 25, 1.06 and 0.11 for callus production, fresh and dry weight, respectively and browning color developing in callus cell culture was observed in this treatment. This result describes the effect the plant hormone 2, 4-D plus active charcoal [61], [62]. However, there was higher browning on callus cell culture in MS medium devoid antioxidant or charcoal, all the callus which produced with citric or ascorbic acid or without were brown in color and turn black after 3–4 weeks.…”
Section: Resultsmentioning
confidence: 90%
“…The explants cultured on plant growth regulator-free MS medium and MS medium containing 3 g/L activated charcoal did not produce calli (Table 1). This may be due to the adsorption of plant growth regulators (2,4-D and kinetin) in medium by activated charcoal (Pan and Van Staden, 1998;Toering and Pullman, 2005;Van Winkle and Pullman, 2005). The percentage of callus induction in MS medium supplemented with 1 mg/L 2,4-D, 0.1 mg/L kinetin, and with or without ascorbic acid was not significantly different.…”
Section: Callus Inductionmentioning
confidence: 99%